Neurological disorders in the Arab world - Benamer, Hani T. S. (Springer International Publishing, 2014)
This book includes all the clinically relevant data on the frequencies and patterns of major neurological disorders among Arabs living in or outside the Arab world. Topics covered include stroke, epilepsy, Parkinson's disease, multiple sclerosis, dementia and headache.  Neurological Disorders in the Arab World is aimed at neurologists who are resident in Arab countries, as well as other physicians who encounter Arab patients, and also researchers performing neuroepidemiological studies. Those responsible for planning and implementing neurological services in Arab countries will also find this book beneficial.